Assessment of structural concrete made by sustainable sand at high temperatures: An experimental research - Mohammad Nadeem Akhtar; Mohammed Jameel; Zainah Ibrahim; N. Muhamad Bunnori (Ain Shams Engineering Journal)
This study assesses the mechanical properties of sustainable sand concrete mixes of DM1*, DM2, DM3, and DM4 by absolute volume method when exposed to elevated temperatures. The concrete specimens were placed in a muffle furnace for two hours at (150–600 °C). Experimental investigations show that the mix strength increases (up to 300 °C), a sudden fall in strength at 450 °C, and a sharp decline at 600 °C was seen. At 600 °C, the highest reduction in compressive and flexural strength of the mixes was reported (21.2, 11.2, 16.6, and 20.4 MPa) and (2.87, 1.41, 2.42, 1.95 MPa), respectively. The concrete mix DM2 with (100 % recycled crushed sand) shows a more significant loss than other mixes. The concrete mix DM4 (50 % recycled crushed sand + 50 % desert sand + 12.5 % silica fume) performs significantly better than other mixes at elevated temperatures. Hence, 100 % recycled crushed sand in structural concrete is not recommended for engineering work.